2007
DOI: 10.2139/ssrn.942378
|View full text |Cite
|
Sign up to set email alerts
|

Winners and Losers: 401(K) Trading and Portfolio Performance

Abstract: Few previous studies have explored how individuals manage their defined contribution (DC) pension plan assets, though these plans constitute an increasingly important component of retirement wealth. Using a valuable new dataset on over one million active 401(k) plan participants in a wide range of plans, we assess the impact of trading on investment performance in DC plans. We find that, in aggregate, the risk-adjusted returns of traders are no different than those of nontraders. Yet certain types of trading s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 21 publications
0
13
1
Order By: Relevance
“…Plan participants also display low levels of financial literacy and investment savvy (Hancock, 2002, Lusardi andMitchell, 2007;Van Rooij, Kool and Prast, 2007); build poorly diversified portfolios (Mottola and Utkus, 2008); overinvest in company stock (Liang and Weisbenner, 2002;Huberman and Sengmueller, 2004;Benartzi, Thaler, Utkus and Sunstein, 2007); and follow their peers (Duflo and Saez, 2002). In previous work, we have also found that excessive trading in 401(k) plans is costly (Yamaguchi, Mitchell, Mottola, and Utkus, 2006). 2 Despite this inventory of possible decision-making errors, few of these studies have attempted to quantify the extent of efficiency losses in the 401 (k) context.…”
mentioning
confidence: 85%
“…Plan participants also display low levels of financial literacy and investment savvy (Hancock, 2002, Lusardi andMitchell, 2007;Van Rooij, Kool and Prast, 2007); build poorly diversified portfolios (Mottola and Utkus, 2008); overinvest in company stock (Liang and Weisbenner, 2002;Huberman and Sengmueller, 2004;Benartzi, Thaler, Utkus and Sunstein, 2007); and follow their peers (Duflo and Saez, 2002). In previous work, we have also found that excessive trading in 401(k) plans is costly (Yamaguchi, Mitchell, Mottola, and Utkus, 2006). 2 Despite this inventory of possible decision-making errors, few of these studies have attempted to quantify the extent of efficiency losses in the 401 (k) context.…”
mentioning
confidence: 85%
“…Plan participants also display low levels of financial literacy and investment savvy (Hancock, 2002, Lusardi andMitchell, 2007;Van Rooij, Kool and Prast, 2007); build poorly diversified portfolios (Mottola and Utkus, 2008); overinvest in company stock (Liang and Weisbenner, 2002;Huberman and Sengmueller, 2004;Benartzi, Thaler, Utkus and Sunstein, 2007); and follow their peers (Duflo and Saez, 2002). In previous work, we have also found that excessive trading in 401(k) plans is costly (Yamaguchi, Mitchell, Mottola, and Utkus, 2006). 2 Despite this inventory of possible decision-making errors, few of these studies have attempted to quantify the extent of efficiency losses in the 401 (k) context.…”
mentioning
confidence: 85%
“…Most commonly this literature has examined who makes these investment decisions (for example Lewellen, Lease, and Schlarbaum 1977;Calvet, Campbell, and Sodini 2007;Guiso and Jappelli 2006) and the performance of the investment decisions in the spirit of the literature examining professional fund manager performance (for example Gruber 1996;Barber and Odean 2000;Barber et al 2003;Gharghoria, Mudumbab, and Veeraraghavanc 2007). A smaller subset of studies has examined the same issues in the context of retirement savings (for example Yamaguchi et al 2006;Clark-Murphy et al 2009;Gerrans 2012). The most common outcome, however, noted in the retirement savings literature has been the lack of decision-making in that most members of retirement savings funds do not make active investment choice decisions (for example Choi et al 2002;Mitchell et al 2006).…”
Section: Literature Reviewmentioning
confidence: 99%